ANALYSIS OF APPROACHES TO THE DEVELOPMENT AND VALIDATION OF THE METHODS OF ANALYSIS OF SOME ACTIVE PHARMACEUTICAL INGREDIENTS FROM THE GROUP OF ANGIOTENSIN CONVERTING ENZYME INHIBITORS IN DRUGS AND BIOLOGICAL LIQUIDS - Logoyda, Liliya (International Journal of Applied Pharmaceutics, 2019)
The quantity of medication brought into the marketplace is growing each year. Analytical method development is increasingly being introduced into fundamental pharmaceutical research and pharmaceutical analysis practice, taking into account their high sensitivity, accuracy, specificity and expressiveness. Search criteria was analytical method development for medicines from group of ACE inhibitors. Literature survey has been done in range of years 1990-2018 to make the review updated and comprehensive and to show the new approacheches to the development of the methods of analysis ACE inhibitors. The sources were world recognized journals and key words used as filter were angiotensin-converting enzyme inhibitors, captopril, enalapril, method development, spectrophotometry, HPLC, UHPLC. The current review is created with an intended to focus on the advantage of HPLC. Literature survey revealed that a number of methods have been reported for estimation of ACE inhibitors individually or in combination with other drugs. However, there is very few analytical methods reported for the simultaneous analysis of these drugs in a combined dosage formulation by HPLC. In additional, analysis of approaches to the development of the methods of analysis of ACE inhibitors in drugs and biological liquids has been shown that HPLC is the most suitable method for analyses ACE inhibitors in substances, drugs, biological liquids to performe routine analysis of medicines, pharmacokinetic (bioequivalence in vivo), dissolution test for final dosages forms (bioequivalence in vitro, biowaiver procedure).